A journey into the heart of workaholism from cross-cultural perspective. (2017) - Sharma, Jyoti; Singh, Abhilasha; Sharma, Parul
The rapid change in today's work practices has made the life of an individual organised around the work. When work takes a disproportionate space in one's life, it may be considered as threat to their well-being. Following the line of research that very limited studies have been conducted to find out the possible culture differences regarding what encourages/discourages the workaholism, the present study has been planned collecting data from 855 employees working in two countries including UAE and India. Applying the discriminant analysis, composition has indicated that in case of India and UAE, employees high on workaholic tendencies experience type-A personality traits. Further, in case of India, employees scoring high on workaholic dimension are females, work in private sector and fall in salary bracket of more than INR 35, 000 per month; whereas in case UAE, employees scoring high on workaholic tendencies experience lesser job characteristics.